2008
DOI: 10.1152/ajpheart.01163.2007
|View full text |Cite
|
Sign up to set email alerts
|

Integrative control of coronary resistance vessel tone by endothelin and angiotensin II is altered in swine with a recent myocardial infarction

Abstract: Several studies have indicated an interaction between the renin-angiotensin (ANG II) system and endothelin (ET) in the regulation of vascular tone. Previously, we have shown that both ET and ANG II exert a vasoconstrictor influence on the coronary resistance vessels of awake normal swine. Here, we investigated whether the interaction between ANG II and ET exists in the control of coronary resistance vessel tone at rest and during exercise using single and combined blockade of angiotensin type 1 (AT(1)) and ET(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 55 publications
1
12
1
Order By: Relevance
“…These observations are similar to our previous reports in normotensive female and male rats (Santos et al 2004). It has been shown that there are gender differences in components of the reninangiotensin system that may play a role in the control of coronary tone (de Beer et al 2008). through an interaction with the renin-angiotensin system (Xu et al 2008).…”
Section: Discussionsupporting
confidence: 92%
“…These observations are similar to our previous reports in normotensive female and male rats (Santos et al 2004). It has been shown that there are gender differences in components of the reninangiotensin system that may play a role in the control of coronary tone (de Beer et al 2008). through an interaction with the renin-angiotensin system (Xu et al 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Flow probes were placed around the proximal left anterior descending coronary artery (2.5-3 mm; Transonic Systems) for measurement of coronary blood flow and the aorta (14 -16 mm; Skalar) for measurement of both cardiac output and stroke volume (33). Finally, in all animals the proximal part of the left coronary circumflex artery (LCx) was exposed, but only in 17 swine that were designated to the MI group the LCx was permanently occluded with a silk suture (7). Three MI swine died during surgery, due to recurrent fibrillation.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Coronary vasomotor tone is tightly regulated by a multitude of vasodilator and vasoconstrictor influences, which, in addition to any direct effects on the vascular smooth muscle, can also impact each others expression, secretion, and receptor activation (7,9,37). After MI, endothelial and neurohumoral control of coronary vasomotor tone is altered (12).…”
Section: Perspective and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is mainly produced in endothelial cells through cleavage from its inactive precursor, Big ET, primarily by ET converting enzyme (ECE) and, to a lesser degree, by chymase, in concert with neutral endopeptidase (NEP) (31). Several studies have shown that ET receptor blockade results in systemic and coronary vasodilation (3,21,32), and hence that ET contributes to basal vascular tone in the systemic vasculature, as well as the coronary circulation. Our laboratory (21) has previously demonstrated that recruitment of coronary flow reserve during exercise is mediated, at least in part, through withdrawal of the vasoconstrictor effect of ET on the coronary vasculature.…”
mentioning
confidence: 99%